Effect of artificial insemination with fresh semen, with one and two services, on the fertility and natality of alpacas - García V., Wilber (2019)
The aim of this study was to evaluate the pregnancy and natality rate of artificial insemination (AI) in alpacas, using fresh semen, with one and two services, in Cusco, Peru. Semen from 10 alpacas was collected by the post-copula method between January and March, using ejaculates that had volume ≥1 ml, motility ≥60% and light red or creamy white color. The ejaculates were diluted in Tris-glucose and egg yolk at a concentration of 20%. For AI, alpacas with history of previous births, ≥20-day post-partum and body condition ≥3, receptive to the male and with a preovulatory follicle ≥7 mm were selected. The induction of ovulation was done with the administration of 80 μg buserelin/animal. The females were inseminated 26-30 h after the induction of ovulation, with diluted fresh semen (1 ml with 25x106 spermatozoa), deposited inside the body of the uterus. The diagnosis of pregnancy was determined at 30 days of service and natality at parturition. Of 200 alpacas inseminated with one service, 50.5% of pregnancy and 46% natality rate were obtained. Likewise, the 99 alpacas that did not conceive at the first service were inseminated for the second time, obtaining 45.5% of pregnancy and 38.4 natality. At the end of the campaign, with 1 or 2 services, 73% of pregnancies and 65% of births were obtained. The high pregnancy and birth rates obtained when inseminating with fresh semen, with one and two services make this technique eligible for use in commercial herds.